Sosialisasi Perancangan Fitur Tunai pada Aplikasi Gapura Mobile di PT PELINDO Cabang Benoa - Merry Royanti Manalu; Made Agung Raharja (Jurnal Pengabdian Informatika, 2026)
Gapura Mobile is an application used by PT PELINDO Cabang Benoa to record vehicle transactions electronically at port gates. However, the application currently lacks an integrated cash receipt reporting feature in the mobile version, making real-time monitoring of cash transactions in the field challenging. This activity aims to design a cash reporting feature that supports accurate, efficient, and integrated transaction recording within the application system. The methods applied include field study, interviews with IT Division staff, feature prototype design, and design socialization for user validation. Based on the evaluation of seven respondents from the IT Division, the feature was rated as easy to use (average score of 4.57) and relevant for supporting cash transaction reporting (average score of 4.00). Interview results also indicate that users expect the feature to assist in audit and daily reporting processes. Therefore, the proposed design is considered appropriate for user needs and holds potential for further implementation by the company’s internal team.